Understanding Children with Autism in ASEAN and Malaysia Through a Public Health Lens: A Scoping Review of Current Research (Bangladesh Journal of Medical Science, 2026)
Autism Spectrum Disorder (ASD) represents a critical public health challenge globally, yet research within the Association of Southeast Asian Nations (ASEAN) region, particularly Malaysia, remains limited and fragmented. Understanding the current landscape of ASD research from a public health perspective is essential to inform evidence-based policy development and improve service delivery for affected individuals and families. This scoping review aimed to systematically map existing research on autism spectrum disorder in ASEAN countries and Malaysia, examining key domains—epidemiology, screening and diagnosis, intervention approaches, and family experiences—through a public health lens. A comprehensive literature search was conducted across multiple electronic databases, including PubMed, Scopus, Web of Science, and Google Scholar, for publications between 2000 and 2024. Studies were included if they addressed ASD from a public health perspective within the ASEAN region. Data extraction captured study characteristics, methodologies, key findings, and public health implications, with thematic synthesis employed to categorize results. This scoping review uncovered several pertinent publications, including a significant portion that specifically addresses Malaysia. Four key research areas were identified: studies on disease prevalence, practices related to screening and diagnosis, various intervention strategies, and the experiences of families. The reported prevalence rates of a particular developmental disorder among children were notably lower than global averages, suggesting considerable underdetection. Delays in obtaining diagnoses ranged widely, exceeding the recommended timeframes. Ongoing challenges included ineffective surveillance systems, insufficient training for healthcare professionals, limited access to proven interventions, cultural stigma, and financial constraints faced by families. Substantial gaps persist in ASD research, policy, and practice within ASEAN and Malaysia. Urgent priorities include establishing robust surveillance systems, implementing universal screening programs, expanding diagnostic and intervention services, developing culturally appropriate support models, and prioritizing autism as a public health imperative requiring comprehensive, coordinated responses across healthcare, education, and social welfare sectors.BJMS, Vol. 25 No. 01 January’26 Page : 28-37